Rationing of Nursing Care and Patient Safety - Witczak, Izabela; Rypicz, Łukasz; Karniej, Piotr; Młynarska, Agnieszka; Kubielas, Grzegorz; Uchmanowicz, Izabella (Frontiers in Psychology, 2021)
Background. Nursing care has a significant impact on patient safety, which affects clinical outcomes, patients’ satisfaction with the care received and nursing personnel’s satisfaction with the care provided. This study aimed to determine the extent of nursing care rationing and its relationship with patient safety including identification of the specific reasons. Methods. This cross-sectional study involved 245 nurses and was performed between April–June 2019 in four hospitals in Wroclaw, Poland. The standardized and relevant research tools such as Hospital Survey on Patient Safety Culture (HSOPSC) and the Perceived Implicit Rationing of Nursing Care (PIRNCA) were used. The data was submitted to hierarchical multiple regression analysis. The study was approved by the Bioethics Committee and was followed with the STROBE guidelines. Results. The PIRNCA scores were negatively correlated with the HSOPSC subscales, which indicates that more frequent rationing of nursing care was associated with lower levels of patient safety parameters. It was shown that the highest level of unfinished nursing care was associated with decreases in patient safety factors linked with supervisor manager expectations actions promoting safety (rs = -.321, p < 0.001), teamwork within hospital units (rs = -.377, p < 0.001), feedback and communication about error (rs = -.271, p < 0.001), teamwork across hospital units (rs = -.221, p < 0.01) and hospital handoffs transitions (rs = -.179, p < 0.01). Moreover, the strongest association was observed between the PIRNCA scores with patient safety grade (rs = 0.477, p < 0.001). Also, the PIRNCA scores among the internal unit were significantly higher than in the intensive care and surgical units. Conclusions. Our study indicated the presence of nursing care rationing. Regarding patient safety, we found insufficient numbers of medical personnel and excessive personnel workload for providing safe care to patients, a lack of transparency in handling adverse event reports and analyses, and a lack of cooperation between hospital units regarding patient safety.